Rhetoric Effect of Ibn Al Faridh’s Poetry Counterparts: اسماء خليل ابراهيم, فرج منسي محمد (Journal of the College of Education for Women, 2020)
The Sufi poetry of Ibn Al-Faridh represents a true image of the spiritual experience, in which he presented the bright aspects of his experience, and his suffering in it, by formulating it in a poetic form, because the Sufi poetry is the result of an experience in which the Sufi seeks to achieve his goal of reaching the truth, and this is why Ibn Al-Faridh made his poetry a tool for expression on his own experience, the poet reflected his Sufi life in which he moved rhymes and weights. The poet Ibn Al-Faridh stands as a witness to his making of Sufi poetry in the service of the purpose of who said, it is the embodiment of the Sufi journey in the stages, and the fluctuation in the places and situations, and it is a psychological, emotional and honorable journey based on depicting the situation of the poor self in the places of gathering and separation, and rhetoric worked wonderfully in its parts, he showed the arts of Al-Badeea as it is an art related to the depth of depiction of gathering and separation, the pain of the self in its separation after the first meeting and its nostalgia for eternal gathering . His poetry appears to have built a solid and intentional structure in which the language has transformed into a harmonious transformation with the sentimental, honorable soul highness. Al-Badeea played an essential role on the level of thought, evidence, and construction, as well as his aesthetic role.